Extending the Determinants of Dollarization in Sub-Saharan Africa: The Role of Easy Access to Foreign Exchange Earnings - Ibrahim D. Raheem; Simplice Asongu (African Governance and Development Institute (AGDI), 2016)
This study argues that the ease at which economic agents have access to foreign earnings would influence/increase the level of dollarization in the economy. The three sources of foreign currency earnings are financial integration, trade openness and natural resource rent. As such, we extend the determinants of dollarization to capture these variables. A dataset of 26 countries in sub-Saharan Africa (SSA) for the period 2001 – 2012 was built. Based on Tobit regression, we found that all the proxies of foreign currency earning, with the exception of natural resource rent, are significant contributors to the increasing rate of dollarization. Specifically, it was found that trade openness and financial liberalization are positive determinants of dollarization, while natural resource rent serves as drag to the dollarization process. These results remain valid to three robustness tests. Policy implications and suggestions for future research were proposed.
Keywords: E31; E41; C21; 330; Dollarization; Openness; Resources; Tobit regression; SSA